Small mammals diversity in three contrasting vegetation in Kelantan - Ean, Wee Chen (2011)
A study on the relative abundance and diversity of small mammals were conducted in three different vegetations in Kelantan. The three different vegetations were durian orchard, regenerated forest and disturbed forest. The collapsible cage traps were used to trap non-volant small mammals. A total of 444 trap-nights for all sites resulted in capture of 30 individuals from three different families. Capture rate for Muridae was 70 percent followed by, 3.33 percent Sciuridae and 26.67 percent Tupaiidae. In this study five species were identified; Tupaia glis (eight individuals), Callosciurus caniceps (one individuals), Rattus rattus (nine individuals), R. tiomanicus (nine individuals) and Maxomys surfer (three individuals). The capture rate at the durian orchard was four percent whereas the regenerated forest and disturbed forest had eight percent capture rate. Shannon index, H' shows that the highest diversity was at regenerated forest (1.3182), followed by disturbed forest (1.2597) and durian orchard (1.0986). Pielau's evenness index showed that the vegetation with the most evenness was durian forest (1.0), followed by regenerated forest (0.9509) and disturbed forest (0.9087). The Simpson's index of diversity shows the highest value durian orchard (0.8), followed by regenerated forest (0.7122) and disturbed forest (0.7576). Comparison of this study with other study run at secondary forest shown satisfactory amount of species capture, but far lower than the high diversity primary forest.